2015
DOI: 10.1002/jsfa.7455
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, partial purification and characterisation of vanillic acid decarboxylase fromAlicyclobacillus acidoterrestrisDSM 3923

Abstract: The present study provides the first report on the characteristics of the VAD from A. acidoterrestris, which will contribute to the development of more effective control methods to minimise A. acidoterrestris-related spoilage in fruit juices. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As its spores can survive conventional heat processes, not only is the pasteurisation insufficient to destroy Alicyclobacillus spores, but also the pasteurised fruit juices could provide abundant nutrition for spores to germinate and grow (Cai et al ., 2015c; Wang et al ., ). The characteristic of the spoilage is the formation of a distinct antiseptic or medicinal off‐odour caused by guaiacol and the halophenols, including 2, 6‐dichlorophenol and 2, 6‐dibromophenol, and guaiacol is the mainly metabolite, which can be detected at a level of 2 μg L −1 by sensory means in fruit juices (Wang et al ., ; Cai et al ., ). It has been reported that Alicyclobacillus acidoterrestris had been isolated from various fruit juices, such as apple, kiwi, pear, grapefruit, lemon, orange, pear, passion, mango and so on, with apple is the most frequent isolation sources (Cai et al ., 2015a; Tianli et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…As its spores can survive conventional heat processes, not only is the pasteurisation insufficient to destroy Alicyclobacillus spores, but also the pasteurised fruit juices could provide abundant nutrition for spores to germinate and grow (Cai et al ., 2015c; Wang et al ., ). The characteristic of the spoilage is the formation of a distinct antiseptic or medicinal off‐odour caused by guaiacol and the halophenols, including 2, 6‐dichlorophenol and 2, 6‐dibromophenol, and guaiacol is the mainly metabolite, which can be detected at a level of 2 μg L −1 by sensory means in fruit juices (Wang et al ., ; Cai et al ., ). It has been reported that Alicyclobacillus acidoterrestris had been isolated from various fruit juices, such as apple, kiwi, pear, grapefruit, lemon, orange, pear, passion, mango and so on, with apple is the most frequent isolation sources (Cai et al ., 2015a; Tianli et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…B. cereus has been widely known as a foodborne pathogenic and a spoilage microorganism able to synthesize proteases, lipases, lecitinases 42 , quitinases 43 , and pectinases 44 . Similarly, A. acidoterrestris is recognized for producing decarboxylases that spoil acidic fruit juices 45 . Nonetheless, this is the first report on A. acidoterrestris colonizing an artwork.…”
Section: Resultsmentioning
confidence: 99%
“…B. cereus has been widely known as a foodborne pathogenic and a spoilage microorganism able to synthesize proteases, lipases, lecitinases [59] , quitinases [60] , and pectinases [61] . Similarly, A. acidoterrestris is recognized for producing decarboxylases that spoil acidic fruit juices [62] . Nonetheless, this is the first report on A. acidoterrestris colonizing an artwork.…”
Section: Resultsmentioning
confidence: 99%